Histopathological assessment of surgical margins of oral carcinomas and related shrinkage of tumour. (18th May 2017) - Sarode, Gargi; Sarode, Sachin C; Shelke, Pankaj; Patil, Shankargouda
The UK Royal College of Pathologists has published widely recognized guidelines that are finding increasing acceptance in the histological assessment of surgical margins of oral squamous cell carcinoma (OSCC). These guidelines are based on the distance of surgical margins from tumour tissue. The results of various published articles indicate that overall shrinkage of OSCC specimens varies from 15% to 75% and depends upon many irrepressible intrinsic and extrinsic factors. In the present article, the intrinsic and extrinsic factors accountable for shrinkage are discussed in depth. A novel basal cell counting method for the assessment of margins and the calculation of shrinkage in OSCC specimens with flat epithelial connective tissue interfaces have also been put forward.